The Influence Of Multiball Training On The Forehand Ability Of Table Tennis Athletes Towarded Ptmsi Pekanbaru - Sayyidatul Mahdiah; Romi Candra (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
The goal to be achieved in this study is to find out how much influence multiball training has on the forehand hitting ability of table tennis athletes assisted by PTMSI Pekanbaru. This type of research is research using the normality test, a method used by researchers to look for causal relationships—also called relationships between two factors—which are deliberately made by eliminating, reducing, or ignoring other disturbing factors. Meanwhile, to determine, under controlled conditions, the effect of the independent variable (treatment/treatment) on the independent variable (outcome. In this study, the variable (X1) is the effect of multiball training, variable (y) is the ability to hit the forehand, the research was carried out at Beautiful Beautiful Gorge marsan on PTMSI Pekanbaru athletes. The time used to carry out this research was for 12 meetings. The sampling was carried out in total sampling, where the population was used as a total sample of 10 coached athlete students. The instrument to be used in this study was a test table tennis backboard.Based on the results of the pree test calculation there is a very good score, namely 1 person with a score of 21, and the results of the post test calculation there is a very good value, namely 1 person with a score of 32. From the results of the pree test and post test calculations the value is very low, namely 0 % .